Feminism and geopolitics through Marvel Cinematic Universe: ideology and history within fantasy in Black Widow, Wandavision and Dr. Strange - Iturregui-Motiloa, Víctor (Historia y Comunicación Social, 2023)
This research proposes, through a narrative and visual analysis, an interpretation of the underlying feminist and geopolitical discourse within the Marvel Cinematic Universe, one of the most successful and popular sagas of the XXIth century. The most interesting aspect lies in the fact that, under the iconography and tropes of fantasy and science fiction, these superheroic stories deal with modern day foreign affairs in the United States, and with social movements such as feminism or #MeToo. Even though it is a constant in many installments of the saga, in the recent films Black Widow and Doctor Strange and in the TV-VOD series Wandavision we can find echoes and allusions to relevant events and characters involved in the history of USA. Thanks to film analysis, we will be able to identify these ideas contained in forms, iconography and narrative strategies.
Keywords: Marvel; Disney; feminism; geopolitics; fantasy; history; USA